A new consonant-vowel architecture: Japanese borrowings from European languages from the viewpoint of Complexity Scales and Licensing - Jaskuła, Krzysztof (Lingua Posnaniensis, 2023)
Japanese has borrowed lexical items from European languages for centuries, mostly for historical and cultural reasons. Phonological analyses concerning the process of importing words from various languages are numerous. Syllabic structures of Western languages usually differ from those in Japanese and this difference manifests itself mainly in the lack of many consonant groups in the latter. In this paper, a number of examples will be provided so as to show how consonant clusters from donor languages undergo decomposition in Japanese loanwords from European languages, also referred to as gairaigo. The phonological model of Complexity Scales and Licensing is employed here with a view to demonstrating precisely why the process of cluster disintegration usually happens, which enforces epenthetic vowels, and why it is at times inhibited.